MENINGKATKAN HASIL BELAJAR SISWA DENGAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) BERBANTUAN MODUL DALAM MATERI LARUTAN PENYANGGA - Apriyani Puspadewi; Syahmani Syahmani (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2016)
Abstract. A research on the use of PBL learning model aided module on material buffer solution which aims to determine (1) the improvement of learning outcomes, (2) adherence to learning activities that teachers do, (3) the student activity and (4) the students' responses to learning. The study design was a classroom action research (PTK) with two cycles. Each cycle consists of planning, action, observation and evaluation, as well as analysis and reflection. The subjects were students of class XI SMA Negeri 1 Banjarmasin MIA with 36 students. Data were collected through observation, achievement test and questionnaire. Data were analyzed by using descriptive analysis of quantitative and qualitative analysis. The results showed that the learning module aided PBL learning model can improve: (1) cognitive learning outcomes of students in the first cycle in the predicate 70.24% 83.50% in quite a good predicate on the second cycle, students in the affective implementation of the actions of 69,03% in the category quite well in the first cycle and 83.21% in both categories at the second cycle and psychomotor students in the implementation of the actions of 67.89% in the category of skilled enough became 79.98% in skilled categories in the second cycle (2) the activities learning by teachers from 76.96% in both categories in the first cycle to 91.85% in the excellent category on the second cycle; (3) the activity of students in the implementation of measures to increase from 71.5% in the active category in the first cycle to 87% in the category of very active in the second cycle; (4) The class XI student of SMAN 1 Banjarmasin MIA responded positively to learning by using a model-assisted PBL modules. Based on research conducted using the model-assisted PBL modules in the buffer solution can increase the activity of the students, the activities of teachers, students affective, psychomotor students and student learning outcomes with the acquisition of a positive response.Keywords: problem based learning, modules, student learning outcomes, buffers